INDIAN FOOD -A NATURAL MEDICINE - chandran R, Theiva; Rani S, Leslie; M.P, Brundha; K, Anjaneyulu (International Journal of Psychosocial Rehabilitation, 2020)
India is the nation of numerous appearances, and this peculiarity is reflected in its ethnic food. Indian food includes a wide assortment of territorial cooking local to India. Given the scope of a wide variety in soil type, atmosphere, and occupations, these cooking styles differ altogether from one another and utilize locally accessible fixings, for example, herbs, vegetables, and organic products. The Indian food routine is noted for its consideration of numerous pulses, spices, and rice, which make this food one of a kind. Being commonly low in fat and high in vegetables, leafy foods, and meat, Indian food has numerous medical advantages. From the British period to this day, Indian food plays an important role in the medical field. This study explores the connection between Indian food and health benefits. The study then looks at the links between the Indian food, Indian medicine, and Indian diet of contemporary India. The study goes on to reflect on the nation's food culture.This review also speaks about some nutritional studies that have been performed to explore different types of food consumed in various Indian regions, among different social samples The paper ends by arguing that Indian food has high medicinal value and a high respect in the medical field.